Handbook of Advanced Nondestructive Evaluation - Ida, Nathan; Meyendorf, Norbert (Springer International Publishing : Imprint: Springer, 2019)
This handbook is a comprehensive source of information on all aspects of non-destructive testing (NDT), for use by professionals, educators, and most of all, by the practitioners of testing. The art of NDT consists of dozens of methods, some classical, and some emerging. As the pace of industrial work and discovery intensifies and materials are utilized to their physical limits, the role of NDT becomes ever more important. As a result, the methods of testing are themselves evolving, and it is the intent of this book to capture this evolution. Handbook of Modern Non-Destructive Testing broadens the scope from traditional books on the subject. In addition to classical, emerging and exotic methods of evaluation, the book will also cover the use of NDT techniques in other fields, such as archaeology or resource exploration. With contributions from experts in all areas of the field, the reader will find balanced coverage of a variety of testing methods, with no bias against or endorsements of any particular method. The book treats many areas in depth, covering all aspects of testing, and will include case studies where appropriate. Additional coverage of statistical methods and their use, as well as simulations' role in testing and test design, are included. .